Family Values Represented in “Enola Holmes” (2020) Movie - Putri Amifalahiya Iqlima (Pro-ELLitera, 2024)
This study aims to identify family relationship values that occur in the Enola Holmes movie. This type of research is a descriptive qualitative study. The data of the research are in the form of observations on Enola Holmes movie which are equipped with the stories in the movie. However, in this study the researcher only analyzes what types of family relationship values occurred in the Enola Holmes movie and the explanation about each value. The results of this study are that there are seven bonding values in family relationship according to Van-wel’s theory, namely attachment, commitment, interdependence, closeness, trust, intimacy, and love. Not only that, the conflict values also occur in this movie based on Pecchioni and Nussbaum’s theory. These values include aggression, disagreement, violence, arguments, and conflict tactics. The number of values in this movie is almost balanced between the positive values (bonding values) and the negative values (conflict values).